Morphology and personal perception of excessive gingival display in anterior maxillary teeth - Nguyen, Thi Phuong Thao; Nguyen, Duc Quynh Trang; Tran, Thien Man; Nguyen, Van Minh (Tạp chí Y Dược Huế, 2025)
Background: An appealing smile is essential for achieving facial harmony. It reflects one’s personality, demeanor, confidence, and essence. The balance of three key components-teeth, gums, and lips contour- contributes to this harmonious expression, fostering comfort and self-assurance in social interactions. However, excessive gingival display, often referred to as a gummy smile, disrupts this balance, leading to aesthetic concerns and impacting psychological well-being and behavior.Materials and methods: A cross-sectional study involving 61 dental students with an anterior gummy smile measured anatomical dimensions related to their smiles in both resting and spontaneous smiling positions. Additionally, students were surveyed about their personal perceptions of their gummy smile condition. Results: In a resting position, the mean height of the midface third, at 59.42 ± 4.23 mm, was significantly less than that of the lower facial third, which measured 68.72 ± 4.80 mm (p < 0.05). The mean gap between the lips at rest was 4.90 ± 2.03mm, and the exposure of the upper central incisors averaged 3.79 ± 1.33 mm. Additionally, the upper lip length was at 21.69 ± 1.87 mm. During spontaneous smiling, the gingival display compared to the upper lip was 4.75 ± 1.00 mm, while the mobility of the upper lip was 6.70 ± 1.60 mm. Regarding personal perception, a gummy smile diminishes patients’ self-awareness, resulting in negative emotional repercussions and impacting quality of life in specific domains, including psychological discomfort and disability. Conclusion: A gummy smile can significantly affect personal perception, emotional well-being, and overall quality of life. More comprehensive research is essential to develop effective treatment strategies that enhance patients’ psychological health, boost their confidence, and improve their aesthetic satisfaction.